Determinants Of Financing For Contemporary Sale And Shirkah Islamic Banking Year 2019-2023 To Quality Profit With NPF As A Moderating Variable - yusuf, muhammad; Jonnedi, Jonnedi; Islami, Ramadahniel; Masril, Masril; Oktaviani , Wulan; Rahmawati, Rahmawati (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
The background of the study is the influence of financing for sale and purchase and syirkah financing which still has a research gap by adding other X variables, namely the addition of financing for sale and purchase and NPF which is one of the disincentives for banks to obtain profit or profit. Regarding the irregular funding indicator as measured by the Net Performance Funding (NPF) ratio. This study aims to analyze financing for sale and purchase which has a significant effect on the Earnings Quality (ROA) of Bank Syariah Indonesia. Let's analyze whether Syirkah Financing has a significant effect on the Earnings Quality (ROA) of Bank Syariah Indonesia. Analyze whether NPF can manage financing for sale and purchase and Syirkah financing with productive ROA quality. This study is based on annual calculations for the period 2019-2023. Using a qualitative descriptive method using a purposive sampling method. In this study, the example is the 2019-2023 financial report. Data collection techniques Documentation Technique and Literature Study were then tested using the SPSS 23.0 test Based on the results of the study, Buying and selling has a significant effect on the quality of income of Bank Syariah Indonesia for the period 2019-2023. There is no significant effect on the quality of profit between Syirkah and Bank Syariah Indonesia in 2019-2023. In the period 2019-2023 there is a significant effect between the quality of NPF income and Bank Syariah Indonesia. Buying and selling and NPF have a significant effect on the quality of profit of Bank Syariah Indonesia in 2019-2023.